Effect of fenestrated stents on the renal arteries: Investigation of hemodynamic changes in abdominal aortic aneurysms treated with fenestrated endovascular grafts. - Sun, Zhonghua; Chaichana, T.; Sangworasil, M.; Allen, Yvonne; Hartley, D.; Lawrence-Brown, M. (ISCIT, 2008)
This article uses a novel method of combining 3D image visualization and computational fluid dynamics to investigate the potential effect of fenestrated stents on the renal arteries in terms of blood flow pattern, flow rate at different cardiac cycles, based on patients with abdominal aortic aneurysm treated with fenestrated stent grafts. 3D imaging appearance of the fenestrated stents inserted into the renal arteries is used to guide the simulation of the stent protrusion into the abdominal aorta model for analysis of hemodynamic changes. A circular stent protrusion with a length of between 5-7 mm inside the abdominal aorta is simulated in two aorta models, and computational fluid dynamics is performed to detect the change of flow pattern and flow rate at the renal arteries. Our results demonstrate change of the renal flow rate is minimal following implantation of fenestrated stents, indicating the safety of fenestrated stent graft repair of patients with aortic aneurysms.